Origin of magmatic and tectonic fabrics in the Remal granite-gneiss, Singhbhum Craton, India. (29th September 2022) - Dobe, Ritabrata; Vukmanovic, Zoja; Bose, Narayan; Panigrahi, Mruganka Kumar; Gupta, Saibal
Abstract: In the Singhbhum Craton of the Indian shield, the Remal granite-gneiss preserves felsic magmatic fabrics onto which a low-temperature segregation layering has been superposed. Planar, sub-horizontal to gently dipping layers (Sign1 ) comprise K-feldspar megacrysts, plagioclase and quartz, with the base of each layer defined by segregations of biotite. Sign2 consists of trough cross-bedded layers composed of K-feldspar phenocrysts, plagioclase and quartz with biotite schlieren defining the base of each layer. Microstructural features such as concentrically arranged mineral inclusions in K-feldspar phenocrysts and graphic intergrowth textures testify to the magmatic origin of these fabrics, with insignificant subsequent metamorphic reconstitution. The tectonic fabric S1 has developed sub-parallel to localized greenschist-facies mylonite bands, and is defined by weakly aligned flakes of biotite. Crystallographic preferred orientations away from the mylonitized domains show a strong alignment of K-feldspar, quartz and biotite parallel to the magmatic fabric due to efficient segregation during magmatic flow. Quartz crystallographic preferred orientations within the mylonitized domains show a strong preferred orientation and dextral asymmetry. Temperature constraints from synkinematic chlorites along with estimates of deformation temperature from quartz crystallographic preferred orientations indicate that mylonitization occurred at the lower limits of quartz crystal plasticity. The results of combined thermodynamic and multiphysics modelling studies show that felsic magmas can undergo significant convective motion for a wide range of crystallinities and water contents before solidification. Additionally, segregation layering resembling a gneissosity can develop at low temperatures owing to localized mylonitization and concomitant dissolution–precipitation of biotite.